Оптимізація реабілітаційних програм в санаторних умовах у пацієнтів первинним гонартрозом зі зниженною мінеральною щільністю кісткової тканини = The rehabilitation programs optimization in sanatorium in patients with primary gonarthrosis with decreasing of bone mineral density - T. G. Bakalyuk (Kazimierz Wielki University, 2016)
Bakalyuk T. G. Оптимізація реабілітаційних програм в санаторних умовах у пацієнтів первинним гонартрозом зі зниженною мінеральною щільністю кісткової тканини = The rehabilitation programs optimization in sanatorium in patients with primary gonarthrosis with decreasing of bone mineral density. Journal of Education, Health and Sport. 2016;6(3):125-139. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.47940 http://ojs.ukw.edu.pl/index.php/johs/article/view/3429 https://pbn.nauka.gov.pl/works/721332   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016.     УДК 616.728.3-06:616.748-007.234]-085.838   THE REHABILITATION PROGRAMS OPTIMIZATION IN SANATORIUM IN PATIENTS WITH PRIMARY GONARTHROSIS WITH DECREASING OF BONE MINERAL DENSITY   T. G. Bakalyuk   I.Ya. Gorbachevsky Ternopil State Medical University, Ternopil, Ukraine   ОПТИМІЗАЦІЯ РЕАБІЛІТАЦІЙНИХ ПРОГРАМ В САНАТОРНИХ УМОВАХ У ПАЦІЄНТІВ ПЕРВИННИМ ГОНАРТРОЗОМ ЗІ ЗНИЖЕННОЮ МІНЕРАЛЬНОЮ ЩІЛЬНІСТЮ КІСТКОВОЇ ТКАНИНИ   Т. Г. Бакалюк ДВНЗ "Тернопільський державний медичний університет імені І. Я. Горбачевського МОЗ України", м.Тернопіль, Україна   Реферат   Проведено дослідження ефективності реабілітаційних програм  у хворих  первинним гонартрозом з явищами остеопенії та остеопорозу. В дослідження включено 132 пацієнти з первинним гонартрозом (ПГА) зі зниженою щільністю кісткової тканини без синовіту, середній вік (61,18±0,74) р., тривалість захворювання (10,07±0,43) р., методом денситометрії у 97 пацієнтів визначено остеопенію, у 35 - остеопороз. Пацієнти були розподілені на 5 груп в залежності від методики застосування сірководневої бальнеотерапії та пелоїдотерапії. З'ясовано, що достовірно позитивний вплив на артрологічний статус, маркери кісткового метаболізму (паратгормон, лужну фосфатазу), цитокіни (IL-1β, ФНП-α, ІL-10)  та показники периферичної  гемодинаміки  мали реабілітаційні програми з включенням різних варіантів сірководневої бальнеотерапії та низькотемпературної пелоїдотерапії. При застосуванні в лікувальному комплексі аплікацій пелоїдотерапії  температурою 38-400С не спостерігалось позитивної динаміки артрологічного статусу: збільшення больового синдрому було відмічено у 28 % пацієнтів досліджуваної групи, обмеження рухів в суглобах у 32 %, зниження повсякденної активності у 44 %, у 22 % не було змін показників артрологічного статусу, покращення досліджуваних показників стану суглобів було відмічено лише у 18 % пацієнтів. Досліджувані цитокіни в цій групі не мали достовірних змін, а показники периферичної гемодинаміки не мали тенденції до покращення. Наші дослідження свідчать про доцільність застосування різних варіантів сірководневої бальнеотерапії в поєднанні з низькотемпературною пелоїдотерпаією для оптимізації реабілітації в санаторних умовах хворих первинним гонартрозом зі зниженною щільністю кісткової тканини.   Ключові слова: остеоартроз, остеопороз, пелоїдотерапія, сірководнева  бальнеотерапія, цитокіни.     THE REHABILITATION PROGRAMS OPTIMIZATION IN SANATORIUM IN PATIENTS WITH PRIMARY GONARTHROSIS WITH DECREASING OF BONE MINERAL DENSITY   T. G. Bakalyuk   I.Ya. Gorbachevsky Ternopil State Medical University, Ternopil, Ukraine   Abstract   Objective of the study - pathogenetic rationale for the use of natural methods in the treatment of osteoarthritis in patients with reduced bone density in sanatorium conditions, to find out the effectiveness of the optimized rehabilitation programs. The study included 132 patients with primary gonarthrosis (PHAs) with low bone density (97 patients - osteopenia, 35 - osteoporosis), without synovitis, the average age (61,18 ± 0,74) years, duration of illness (10,07 ± 0,43) years. Visual analogue scale, a questionnaire to determine functional index Lequesne and WOMAC questionnaire were used to assess the arthrological status. The amount of active and passive movements in the joint evaluated in degrees using the protractor. The peripheral hemodynamics was investigated by tetrapolar rheovasography. The study tested blood serum mineral metabolism (total content of calcium and inorganic phosphorus), markers of bone formation (alkaline phosphatase, parathyroid hormone), proinflammatory cytokines IL-1β, TNF-α and anti-inflammatory cytokine IL-10 (pg / ml). Patients were distributed by randomization into 5 groups according to the methods of application of hydrogen sulfide balneotherapy and pelotherapy. It has been established that the rehabilitation program with inclusion of different options of hydrogen sulfide balneotherapy and low-temperature pelotherapy had significantly (p<0.05) positive effect on arthrologic status, parathyroid hormone, alkaline phosphatase, IL-1β, IL-10 and on the performance of peripheral hemodynamics. The use of pelotherapy applications temperature 38-40°C in the rehabilitation complex had negative dynamics of arthrologic status due to the increase pain in 28 % of patients in the study group, restriction of movements in the knee joints in 32 %, daily activity reduction in 44 %, unchanged artrological status in 22%, only 18% patients of this group marked improvement of studied indicators of joints.